THE INFLUENCE OF SALES PROMOTION, UTILITARIAN, SELF ESTEEM, AND HEDONIC MOTIVE ON PURCHASE DECISION WITH IMPULSE BUYING AND BEHAVIOR INTENTION AS VARIABLE INTERVENINGS IN SHOPEE IN GEN Z - Virnanda Laraswati; Indrawati (PT. Jurnal Center Indonesia Publisher, 2025)
This research aims to understand the influence of Sales Promotion, Utilitarian, Self-Esteem, and Hedonic Motive on Purchase Decisions with Impulse Buying and Behavior Intention as intervening variables in Shopee. The research method used is quantitative with a descriptive approach using a Likert scale. Using the SEM data analysis method. The population of this study is Shopee application users in Indonesia, especially generation Z (1997-2012), with 285 respondents taken using non-probability sampling techniques. The research results show that Sales Promotion, Utilitarian, Self-Esteem, and Hedonic Motive have a positive effect on Purchase Decision. Apart from that, Sales Promotion also has a positive effect on Impulse Buying and Behavior Intention. The implication of this research is that companies can utilize the Self-Esteem motive to improve purchasing decisions. Personalized product recommendations and price offers that match consumer preferences can be implemented to increase consumer satisfaction and trust. Implementing algorithms can help companies provide better shopping experiences, improve purchasing decisions, and strengthen consumer behavioral intentions